CITY: MAPS, AN INTEGRATED SYSTEM BETWEEN PASCAL AND AUTOCAD (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this papar ,we designed a system that deals with comnmintymaps for cities. It depend on the integration style amon. It depend on the integration style amongest more than one application Language of different purposes to be used at run time to perform acommon task . we made use ofthe available facilities in the autocad system and its grand potentials to draw the map elements and processes them for the enlargement and zomming It makes use of the facilities in programmibg language pascal on dealing with files to form a data base system where a special use has been made of operating system shell to achieve integration and communication to tl'ansfere beteeen autocad and pascal according to system needs.